IDENTIFIKASI PENAMPILAN REPRODUKSI SAPI BALI (Bos sondaicus) BETINA SEBAGAI AKSEPTOR INSEMINASI BUATAN UNTUK MENUNJANG PROGRAM UPSUS SIWAB DI KABUPATEN BADUNG DAN TABANAN - Suranjaya I G.; N. P. Sarini; A. Anton; A. Wiyana (Majalah Ilmiah Peternakan, 2019)
This research was conducted in Badung and Tabanan Regencies with a survey method on bali cow farmer groupwhere the cows as artificial insemintion (AI) acceptors were in the the program of special effort on acceleration ofpregnant cattle and buffalo population (Upsus Siwab). Sampling was carried out by purposive random samplingwith 74 cows were in Badung and 61 cows were in Tabanan. Data obtained from interviews and recording fromfarmers, farmer groups and inseminator staffs. Data collected included: age of cows, age of first mated, calvingrate, service per conception, gestation period, and post partus heat. Data generated were analysed using descriptivestatistics and reproductive performance of bali cows as AI acceptors between Badung Regency and Tabanan Regencywas analysed using Two Independent Sample T Test. Results showed that the average age of cows in Badung andTabanan was 4.23 ± 2.00 years and 4.50 ± 2.90 years and the age at first mated was 1.74 ± 0.49 and 1.900.38 yearsrespectively. Calving rate of cows as AI acceptors in Badung and Tabanan Regencies were 56.75% and 40.98%respectively. Service per conception is 1.62 ± 0.39 times and 1.90 ± 0.38 times, respectively. The average of gestationperiod of cows in Badung 9.63 ± 0.52 months tended to be longer than of 9.45 ± 0.22 months in Tabanan, whereasthe post partus heat were 3.06 ± 0.94 months and 3.53 ± 1.03 months, respectively. In conclusion, the calving rate ofcows in Badung was greater than of in Tabanan and the post partus heat of AI acceptor cows in Badung was shorterthan of in Tabanan.